Simulation Model of a Node for Smart Grid Applications, Equipped with Photovoltaic Panel, Energy Storage and Electric Vehicle - Damiani, Lorenzo; Dellachà, Jacopo; Prato, Alessandro Pini; Revetria, Roberto (Journal of Technology Innovations in Renewable Energy, 2014)
The improvement of renewable energy sources exploitation is a central topic of the present studies in the energetic field. One of the main obstacles to the renewable energy increase in the global energetic mix is represented by the fluctuating nature of renewable power sources. The power fluctuations are cause of stress for the electric grid to which the individual nodes are connected. A wider exploitation of renewable power is possible through the implementation of a “smart grid”, constituted by an interconnection of several smart nodes consisting in a user and a renewable source. To reduce the stochastic effects of the renewable energy source it is possible to introduce in the nodes composing the smart grid an energy storage, finalized to smooth the power peaks, rending the node itself less disturbing for the electric grid. This paper presents a simulation model of a smart node, consisting in a user power profile, a photovoltaic panel, an electric vehicle and a battery. Through the simulation model it is possible to evaluate the node effect on the electric grid, with a quantitative approach. Tests were worked out in different node configurations: basic (the only user power profile), basic with photovoltaic panel, basic with storage, basic with panel and storage and finally the complete configuration including also the electric vehicle. The tests were repeated for a domestic and an industrial user to evaluate the size influence over the parameters of interest